Agronomic performance and yield stability of elite white Guinea yam (Dioscorea rotundata) genotypes grown in multiple environments in Nigeria - Olatunji, A.A.; Gana, A.S.; Tolorunse, K.D.; Agre, A.P.; Adebola, P.; Asfaw, A. (MDPI, 2024)
Yam (Dioscorea spp.) is a main staple tuber crop in Nigeria and the West African region. Its performance is determined by genotypes and also the environment of growth. This study assessed the agronomic performance and yield stability of elite white yam (Dioscorea rotundata) genotypes across diverse Nigerian environments. A total of 25 genotypes were evaluated at three locations in two consecutive growing seasons, 2022 and 2023, for fresh tuber yield, disease resistance, and tuber quality traits. The genotype’s performance and stability for the measured traits were assessed using various analytical tools such as additive main effects and multiplicative interaction (AMMI) and multi-trait stability index (MTSI). The AMMI analysis revealed significant differences among the genotypes and across the environments for all traits (p < 0.001, p < 0.01). The PCA revealed that the first two principal components (PC1 and PC2) explained a substantial portion of the total variation (49.84%). The MTSI identified four clones: G18, G19, G24, and G16 as promising candidates for improved yam production in Nigeria with high and stable performance for the multiple traits.